Medicinal evaluation and molecular docking study of osajin as an anti-inflammatory, antioxidant, and antiapoptotic agent against sepsis-associated acute kidney injury in rats - Mohammad Alhilal; Huseyin Serkan Erol; Serkan Yildirim; Ahmet Cakir; Murat Koc; Suzan Alhilal; Esra Dereli; Omer Alkanoglu; Volkan Ay; Ismail Can; Mesut Bunyami Halici (Renal Failure)
Despite efforts to find effective drugs for sepsis-associated acute kidney injury (SA-AKI), mortality rates in patients with SA-AKI have not decreased. Our study evaluated the protective effects of isoflavone osajin (OSJ) on SA-AKI in rats by targeting inflammation, oxidative stress, and apoptosis, which represent the cornerstones in the pathophysiological mechanism of SA-AKI. Polymicrobial sepsis was induced in rats via the cecal ligation and puncture (CLP) technique. Markers of oxidative stress were evaluated in kidney tissues using biochemical methods. The expression of interleukin-33 (IL-33), 8-hydroxydeoxyguanosine (8-OHdG), caspase-3, and kidney injury molecule-1 (KIM-1) was evaluated as indicators of inflammation, DNA damage, apoptosis, and SA-AKI respectively in the kidney tissues using immunohistochemical and immunofluorescent detection methods. The CLP technique significantly (p < 0.001) increased lipid peroxidation (LPO) levels and significantly (p < 0.001) decreased the activities of superoxide dismutase and catalase in kidney tissues. In the renal tissues, strong expression of IL-33, 8-OHdG, caspase-3, and KIM-1 was observed with severe degeneration and necrosis in the tubular epithelium and intense interstitial nephritis. In contrast, the administration of OSJ significantly (p < 0.001) reduced the level of LPO, markedly improved biomarkers of antioxidant status, decreased the levels of serum creatinine and urea, lowered the expression of IL-33, 8-OHdG, caspase-3, and KIM-1 and alleviated changes in renal histopathology. A promising binding score was found via a molecular docking investigation of the OSJ-binding mode with mouse IL-33 (PDB Code: 5VI4). Therefore, OSJ protects against SA-AKI by suppressing the IL-33/LPO/8-OHdG/caspase-3 pathway and improving the antioxidant system.